Presentasi Oral O-001 s/d O-050 Hlm 11-109 - Jurnal Hemera Zoa (Hemera Zoa, 2016)
Presentasi Oral O-001 s/d O-050 Hlm 11-109 Prosiding KIVNAS Ke-14 PDHI 2016 di ICE, BSD City, Serpong, Tangerang Selatan.